Strength properties of concrete with metallic dust wastes as substitute for fine aggregates - Bron, Martin Teotimo C. (Animo Repository, 2016)
In this study the use of metal aggregate from blacksmith forging wastes were used as recycled materials as partial substitute for concrete mixing and to determine if it will affect the strength properties of concrete. The metal aggregates were characterized using results from scanning electron microscope (SEM), energy dispersive X-ray spectroscopy and particle size distribution. Metal aggregates were used to replace sand as fine aggregates in concrete mixing at 0%, 25%, 50% and 75% by volume substitution. Concrete mixing was done in accordance to ASTM Standards and cured at 7, 14, 21 and 28 days. The testing results showed that there is improved performance in the compressive strength for the concrete specimen with 25% of metallic dust wastes. The increase in compressive and splitting tensile strength was brought by the micro-filling effect of the finer particles of the metallic dust wastes as compared to the sand aggregate. The micro-filling effect reduces the transition zone of the paste-to-aggregate in the concrete which makes the concrete less permeable. However, further increasing the percent substitution would lead to drastic decrease in the workability and strength. The finer particles of the metallic dust wastes require more water to wet its larger surface area causing lack of water for the active materials in the mix to hydrate. With the use of metallic dusts wastes as partial substitute to sand, it would be best to keep the percent substitution at 25% to limit the decrease in workability and maximize the strength of the concrete.